1983
DOI: 10.1021/bi00274a047
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships in the dodecapeptide .alpha. factor of Saccharomyces cerevisiae

Abstract: Ten analogues of His-Trp-Leu-Gln-Leu-Lys-Pro-Gly-Gln-Pro-Met-Tyr, the dodecapeptide alpha factor of Saccharomyces cerevisiae, were synthesized by conventional solution phase techniques and purified by using high-performance liquid chromatography. The dodecapeptide was also synthesized attached at its carboxyl terminus to poly(ethylene oxide), a macromolecular protecting group. Analogues in which Lys6 or His1 was modified exhibited high biological activity as evidenced by their ability to elicit aberrant morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 13 publications
3
41
0
Order By: Relevance
“…For simplicity, we use the abbreviated notations: the natural a-mating factor is denoted as (1 -13)peptide, and the des-Trp' dodecapeptide as (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)peptide. Thus, truncated peptides are denoted with the numbering of the N-terminal and C-terminal residues.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For simplicity, we use the abbreviated notations: the natural a-mating factor is denoted as (1 -13)peptide, and the des-Trp' dodecapeptide as (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)peptide. Thus, truncated peptides are denoted with the numbering of the N-terminal and C-terminal residues.…”
Section: Methodsmentioning
confidence: 99%
“…It may readily be noted that these peptides are classified into three groups, A,, A, and B, from the spectral patterns of amide proton resonances, especially in the region 8.5 -8.0 ppm. The group B includes the inactive analogs, (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), (3)(4)(5)(6)(7)(8)(9)(10) and his^] (1 -13)peptide, and a number of N-H proton resonances of this group are localized around 8.4-8.3 ppm. The group A, includes active (1-n)peptides (n = 13, 12 and 10) and inactive (1 -9)peptide, and the group A, includes active (2-n)peptides ( n = 13 and 12) and inactive (2-9)peptide.…”
Section: Spectral Pattern Of Amide Proton Resonancesmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous report found that dodecapeptide α-factor extended at the C-terminus with non-amino acids such as polyethylene glycol (PEG) is neither active in morphogenesis assay nor binding assay. 4,49 Therefore, the fairly high affinity of Cterminal extended analogs 1-6 ranging from 10% to 70% compared to that of native pheromone indicated that Trp extension has certain additional effects upon receptor binding. These effects include penetration of the ligand toward receptor site 1, which is the hydrophobic C-terminal binding pocket surrounded by transmembrane domain helix bundles.…”
Section: 1042mentioning
confidence: 99%